Báo cáo hoạt động của Nhóm nữ đại biểu Quốc hội năm 2014 và dự kiến hoạt động năm 2015. - Nguyễn Thúy Anh (2014)
Báo cáo hoạt động của Nhóm nữ đại biểu Quốc hội năm 2014 và dự kiến hoạt động năm 2015.